Effect of One versus Two Drain Insertion on Postoperative Seroma Formation after Modified Radical Mastectomy - ebrahimifard, farzaneh (Novelty in Biomedicine, 2016)
Background: Modified radical mastectomy (MRM) is still one of globally accepted surgical techniques for breast cancer and in some selected patient is the gold standard type of surgery. The most frequent complication of this procedure is seroma under skin flaps or in the axilla as reported as much as 30% in some studies. The use of closed suction drainage system to reduce the incidence of this complication has been routinely accepted by surgeons; however, length of catheter stay and the number of catheters inserted in the wound are still controversial. The present study compares the results of single versus double drain insertion in patients undergoing MRM for breast cancer. Materials and Methods: The study was conducted on 100 women with breast cancer who were candidate for MRM surgery during 2007-2010 referred to Modarres hospital, Tehran, Iran as a randomized group matched controlled trial. Results: There was no significant difference between the two groups in terms of age, BMI, and tumor weight (P=0.406) (Table 1). Similarly, the difference between the two groups was insignificant in tumor size (T) and number of lymph nodes involved (P=0.145). There was no significant difference between the two groups in timing of axillary drain removal (P=0.064). No significant differences were observed between the two groups in mean aspirated fluid (P=0.071) and mean aspirated sera (P=0.484) after removal of drains. Conclusion: This study revealed one drain insertion in MRM surgery is as effective as two drain and probably less morbidity and cost.